High fat diet-induced hyperglycemia: prevention by low level expression of a glucose transporter (GLUT4) minigene in transgenic mice. - Ikemoto, S (1995)
High-fat intake leading to obesity contributes to the development of non-insulin-dependent diabetes mellitus (NIDDM, type 2). Similarly, mice fed a high-fat (safflower oil) diet develop defective glycemic control, hyperglycemia, and obesity. To assess the effect of a modest increase in the expression of GLUT4 (the insulin-responsive glucose transporter) on impaired glycemic control caused by fat feeding, transgenic mice harboring a GLUT4 minigene were fed a high-fat diet. Low-level tissue-specific (heart, skeletal muscle, and adipose tissue) expression of the GLUT4 minigene in transgenic mice prevented the impairment of glycemic control and accompanying hyperglycemia, but not obesity, caused by fat feeding. Thus, a small increase (< or = 2-fold) in the tissue level of GLUT4 prevents a primary symptom of the diabetic state in a mouse model, suggesting a possible target for intervention in the treatment of NIDDM.